Effect of different palatal vault shapes on the dimensional stability of glass fiber-reinforced heat-polymerized acrylic resin denture base material - Dalkiz, Mehmet; Arslan, Demet; Tuncdemir, Riza Ali; Bilgin, Selim M; Aykul, Halil (European Journal of Dentistry, 2012)
Objective: The aim of this study was to determine the effect of different palatal vault shapes on the dimensional stability of a glass fiber reinforced heat polymerized acrylic resin denture base materialMethods: Three edentulous maxilla with shallow, deep and medium shaped palatal vaults were selected and elastomeric impressions were obtained. A maxillary cast with four reference points (A, B, C, and D) was prepared to serve as control. Point (A) was marked in the anterior midline of the edentulous ridge in the incisive papillary region, points (B) and (C) were marked in the right and left posterior midlines of the edentulous ridge in the second molar regions, and point (D) was marked in the posterior palatal midline near the fovea palatina media (Figure 2). To determine linear dimensional changes, distances between four reference points (A-B, A-C, A-D and B-C) were initially measured with a metal gauge accurate within 0.1 mm under a binocular stereo light microscope and data (mm) were recordedResults:No significant difference of interfacial distance was found in sagittal and frontal sections measured 24 h after polymerization and after 30 days of water storage in any of experimental groups (P>05). Significant difference of linear dimension were found in all experimental groups (P<.01) between measurements made 24 h after polymerization of specimens and 30 days after water storageConclusion: Palatal vault shape and fiber impregnation into the acrylic resin bases did not affect the magnitude of interfacial gaps between the bases and the stone cast surfaces. (Eur J Dent 2012;6:70-78)
Keywords: Acrylic resin denture base; denture reinforcing fiber; polymerization; dimensional stability; palatal vault shape